Technical and environmental feasibility of Laguna Lake water abstraction for domestic water use - Dimas, Dianne Charmaine C.; Herrera, Eugene C. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
The continuously rising demand in water, together with the risks on the operating life of Angat Dam have resulted to MWSS and the two private concessionaires, Manila Water and Maynilad to seek alternative water supply sources, and then they found the Laguna Lake. However, too much abstraction of water from the lake may aggravate the saltwater intrusion in the lake during Pasig River backflows which may give rise to various conflicts to the lake's users. This research is focused on setting up a hydraulic model that can run different abstraction simulations and to provide some scenarios that can be used as guide to set the limits in abstracting water in the Laguna Lake for domestic water supply use. This is done by using 3D hydrodynamic modeling software, Delft 3D to set-up the model of the lake. The model is calibrated using the lake and Pasig River's manning roughness coefficient and validated using water level and water currents. Different scenarios are simulated in the model by varying the location and rates of the abstraction points. Results of the simulations show that abstracting water from the West Bay initially affects the other areas of the lake less than the other simulations. However, result from the 3000 MLD abstraction at West and Central Bay yields a salinity of 4.07 ppt and 4.54, respectively. This is above the limit of salt concentration for drinking water which is 1 ppt, so the water treatment process for the lake water from this bay requires to be more intense and generates higher expenses because the West Bay is the most polluted area of the lake. On the other hand, abstracting water from the Central and East Bay may cost less because these areas contain the relatively cleaner water of the lake. However, conflicts between lake users may arise because saltwater intrusion from this point affects the agricultural lands in the Talim Island and Rizal. Almost all the results of the scenarios yields a salinity concentration within the limit. Lastly, the South Bay can be an ideal location to abstract water because the saltwater intrusion from this point does not affect other areas much. The result of the 1000 MLD abstraction at this location generates zero salinity near the abstraction point at the other bays. This location has a great potential to be used as a location of water abstracting at high rates. Recommendation from this study includes the re-operation of the Napindan Hydraulic Control Structure because the saltwater intrusion is aggravated by the water abstraction no matter at what location or rate the abstraction. Re-operating the NHCS will increase the potential of the lake to be used as a drinking water supply source. Another recommendation is to avoid or decrease rates of abstractions during the dry season in order not to intensify the natural saltwater intrusion to the lake thru Pasig River backflows.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Water withdrawals -- Environmental aspects; Water withdrawals -- Philippines; Laguna de Bay (Philippines).